A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from the River Cauvery, Karnataka, India - Muthukatturaja, Marimuthu; Balasubramanian, Chellaiah; Selvakumar, Chellappa; Murali, Palraju (Zootaxa, 2025)
Choroterpes (Euthraulus) kanagae sp. nov. is described based on larvae and male imago, collected from the River Cauvery, Karnataka, India. The new species is differentiated from other known species of the subgenus Euthraulus Barnard, 1932 by the following combination of characters: posterior margin of abdominal terga I–VII with a dark brown band; tergalius I absent; dorsal lamella of tergalius VII with two terminal processes; costal projection of hind wing acute; segment I of gonostylus slender without inner-apical angle; penis slender, elongated, little longer than ½ of gonostylus length. Comparison of larvae and male imaginal characters of known species of Indian Choroterpes (Euthraulus) are provided. Mitochondrial cytochrome oxidase subunit I (COI) gene was amplified from larva and adult, and compared with published sequences of related species.